2023
DOI: 10.3389/fbioe.2023.1111882
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of hydrogels as delivery systems and scaffolds in the treatment of secondary spinal cord injury

Abstract: Secondary spinal cord injury (SSCI) is the second stage of spinal cord injury (SCI) and involves vasculature derangement, immune response, inflammatory response, and glial scar formation. Bioactive additives, such as drugs and cells, have been widely used to inhibit the progression of secondary spinal cord injury. However, the delivery and long-term retention of these additives remain a problem to be solved. In recent years, hydrogels have attracted much attention as a popular delivery system for loading cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 151 publications
0
19
0
Order By: Relevance
“…The scaffolds must also incorporate trophic factors, cells, agents, and other relevant components. Furthermore, the scaffolds should possess the ability to direct axon development and facilitate cell proliferation ( Peng et al, 2023 ). Scaffold materials must offer an optimal milieu for the processes of cell adhesion, proliferation, and differentiation.…”
Section: Application Of Biomaterials Scaffolds In Scimentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffolds must also incorporate trophic factors, cells, agents, and other relevant components. Furthermore, the scaffolds should possess the ability to direct axon development and facilitate cell proliferation ( Peng et al, 2023 ). Scaffold materials must offer an optimal milieu for the processes of cell adhesion, proliferation, and differentiation.…”
Section: Application Of Biomaterials Scaffolds In Scimentioning
confidence: 99%
“…Hydrogel is a type of biomaterial that has properties akin to those of gelatinous substances. Its primary purpose is to facilitate medication and cell transportation ( Peng et al, 2023 ). Hydrogel exhibits favorable injectability and recoverability, rendering it suitable for administering chemicals to facilitate SCI healing.…”
Section: Application Of Biomaterials Scaffolds In Scimentioning
confidence: 99%
“…In the tissue engineering for the treatment of SCI, the role of hydrogels mainly includes the following points: Firstly, hydrogels provide three-dimensional spatial support for neuronal regeneration and axonal extension, which is conducive to cell growth, proliferation and migration and promotes neural reconstruction ( Chedly et al, 2017 ; Silva et al, 2023 ). Secondly, the hydrogel itself act as a carrier to load stem cells to the site of injury, reducing cell loss to surrounding tissues and off-targeting ( Peng et al, 2023 ). Thirdly, hydrogels slowly release bioactive factors or chemical drugs to achieve a sustained and stable release for better performance ( Luo et al, 2021 ; Figure 2 ).…”
Section: Application Of Hydrogels In Sci Repairmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a major medical condition worldwide, often resulting in motor dysfunction and chronic pain syndromes. , Approximately one million people worldwide have been reported to suffer from SCI-related disorders each year, with traumatic contusions being the most common. , Traumatic SCI includes primary injury and secondary injury . Many studies have reported that secondary injury is an important stage in the treatment of SCI. , Timely therapeutic intervention can inhibit the progression of secondary injury and have a significant impact on long-term neurological and functional recovery . The spinal cord microenvironment in the secondary injury phase produces large amounts of reactive oxygen species (ROS) (e.g., H 2 O 2 ). , The ROS cannot be metabolized in a timely manner and form accumulation, leading to local ischemia, hypoxia, and inflammatory cascade response .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Timely therapeutic intervention can inhibit the progression of secondary injury and have a significant impact on long-term neurological and functional recovery. 8 The spinal cord microenvironment in the secondary injury phase produces large amounts of reactive oxygen species (ROS) (e.g., H 2 O 2 ). 9,10 The ROS cannot be metabolized in a timely manner and form accumulation, leading to local ischemia, hypoxia, and inflammatory cascade response.…”
Section: Introductionmentioning
confidence: 99%